2017
DOI: 10.1016/j.ihj.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The association of the Syntax score II with carotid intima media thickness and epicardial fat tissue

Abstract: AimSyntax score II (SSII) is a highly predictive scoring system, which is used to improve individualized assessment of patients with complex coronary artery disease and facilitates clinical decision making. Surrogate markers [carotid intima-media thickness (CIMT), epicardial fat tissue (EFT)] are also used for risk assessment, but their relation with SSII is not well established.MethodWe enrolled 543 consecutive patients, who underwent coronary angiography for stable angina pectoris and acute coronary syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…Avci et al found a positive correlation between Syntax score I, three-vessel disease, and carotid stenosis [26]. A similar correlation between the intima-media thickness of the carotid artery and Syntax score I and II was reported by the teams of Saedi et al, Ikeda et al, Aksu et al, and Korkmaz et al [27], [28], [29], [30]. The results of Ozturk and Sahin and Costanzo et al and col [31], [32], [33] are opposing.…”
Section: Discussionsupporting
confidence: 53%
“…Avci et al found a positive correlation between Syntax score I, three-vessel disease, and carotid stenosis [26]. A similar correlation between the intima-media thickness of the carotid artery and Syntax score I and II was reported by the teams of Saedi et al, Ikeda et al, Aksu et al, and Korkmaz et al [27], [28], [29], [30]. The results of Ozturk and Sahin and Costanzo et al and col [31], [32], [33] are opposing.…”
Section: Discussionsupporting
confidence: 53%
“…Several studies demonstrated a close association between CIMT and SS I [9-11] . A recent study showed that CIMT correlated with SS II [12] . Two previous studies concluded that SS I is not a predictor of CAS [13,14] .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between SS II and CrAD provides an advantage for having an opinion about CrAD without imaging. Aksu et al 26 investigated the relationship between SS II and carotid intima–media thickness (cIMT) and epicardial fat tissue (EFT). The authors compared low and high SS II groups after they had specified a median SS II value.…”
Section: Discussionmentioning
confidence: 99%